Analisis Perbedaan Tingkat Kebugaran Jasmani Mahasiswa Semester 1 Kelas A dan Mahasiswa Semester 1 Kelas B di STKIP Muhammadiyah Sungai Penuh - Anggil Jufinda (Peneliti.net, 2023)
The problem in this research is the physical fitness of STKIP Muhammadiyah Sungai Penuh students. The type of research used is comparative. The population in this study were all students of STKIP Muhammadiyah Sungai Penuh, totaling 498 students and purposive sampling based on a consideration by the author, where there were 28 students. Based on the results of the research on the level of physical fitness of STKIP Muhammadiyah Sungai Penuh students, Semester 1 Class A with students of STKIP Muhammadiyah Sungai Penuh Semester 1 Class B, the Sports Education Study Program used a difference test (t-test), obtained tcount (0.688) > t-table (1.684), so that Ha was rejected and H0 was accepted, so the conclusion was that there was no difference in the level of physical fitness of students of STKIP Muhammadiyah Sungai Penuh Semester 1 Class A with students of STKIP Muhammadiyah Sungai Penuh Semester 1 Class B Sports Education Study Program.